The Strategic Role of the HR Department in Increasing the Company's Competitive Advantage (Case Study of Madura Batik Jokotole Collection) - Sabna Tunnabila; Makkiyah; Mohammad Maksum; Iriani Ismail (PT FORMOSA CENDEKIA GLOBAL, 2023)
Excellence in competition is greatly influenced by human resource management strategies. By implementing appropriate human resource management strategies, it is hoped that companies can utilize the advantages of their human resources to support the achievement of competitive advantage. In the context of this phenomenon, the author feels interested in conducting research on the Jokotole Collcetion Madura batik company using a qualitative approach. The results of this research indicate that human resource management has a key role in linking company strategy with performance achievement, organizational culture development, innovation, and flexibility.